Tuning the Properties of Polyvinylidene Fluoride/Alkali Lignin Membranes to Develop a Biocatalytic Membrane Reactor for an Organophosphorus Pesticide Degradation - Serena Regina; Giuseppe Vitola; Rosalinda Mazzei; Lidietta Giorno (Membranes)
It has been observed that the immobilization of a phosphotriesterase enzyme (PTE) onto polyvinylidene fluoride (PVDF) membranes significantly decreased the enzyme activity, and this negative effect was attributed to the hydrophobic character of the membrane. The indirect indication of this reason was that the same enzyme immobilized on other membrane materials bearing hydrophilic character showed better performance. In this work, we provide direct evidence of the mechanism by immobilizing a PTE on a PVDF membrane hydrophilized by blending it with alkali lignin (AL). The PTE was immobilized on PVDF membrane by a covalent bond with the same procedure used in earlier studies to attribute changes in enzyme activity solely to the wettability properties (and not to the material chemistry). The activity of the PTE immobilized on the PVDF membrane hydrophilized with AL was 50% higher than that of the enzyme immobilized on the PVDF hydrophobic membrane. Further improvements of the membrane structure tailored for the development of a biocatalytic membrane reactor (BMR) were also promoted. In particular, the performance of the BMR was studied as a function of the thickness of the membrane, which allowed us to modulate the residence time into the enzyme-loaded membrane pores while maintaining the flow rate through the pores at a constant.